(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Aggression is an action. It is intended to harm someone.It can be a verbal attack–insults, threats, sarcasm, or attributing nastymotives to them–or a physical punishment or restriction. Aggression also seemsto be a way of maintaining social order among many species. Animals competewith each other over food, mates, and dwelling spaces, often showing aggressionand occurring among virtually all vertebrate species, including humans. However,if aggression is an effective way of maintaining social order, recklessviolence appears to be a poor survival mechanism. Nevertheless, this trait hasnot been wiped out. Since it hasn’t disappeared, it is logical that researchershave tried to understand the nature of this behavior. In doing this, there hasbeen an ongoing argument of what its source is. One need only pick up the dailynewspaper to see how serious a problem violence is in today’s society. Althoughthe incidence of violent behavior in the US has fallen significantly in thepast few years, there is still about an 80% chance that a person will be thevictim of a violent crime during his or her lifetime. Even more troubling isthe trend of increasing violence among the very young.